Genetic diversity of Cryptosporidium identified in clinical samples from cities in Brazil and Argentina - Saramago Peralta, Regina Helena (2016)
Fil: Saramago Peralta, Regina Helena. Universidade Federal Fluminense. Faculdade de Medicina. Departamento de Patologia; Brasil.